Industrial IoT technologies and applications : International Conference, Industrial IoT 2016, GuangZhou, China, March 25-26, 2016, Revised selected papers /: International Conference, Industrial IoT 2016, GuangZhou, China, March 25-26, 2016, Revised selected papers. (2016) - Unknown
No abstract available